Career Development and Performance of Non-Family Employees in Selected Family-Owned Businesses in Kenya: West Kenya Sugar and Kirathimo Cereals - Gathenge, Jedida; Obere, Eliud (European Scientific Journal, ESJ, 2021)
Non-family employees in family organizations may face career development challenges. The study explores the impact of employee promotion, training, and assessment practices on the performance of nonfamily employees within family-owned organizations. The study applied a mixed-methods approach. The target population was from two family-owned businesses in Kenya, West Kenya Sugar, and Kirathimo Cereals. Using a cluster sampling approach, 106 participants took part in the study. The results indicated a positive and significant impact of employee training on employee performance (β = 1.049, t = 8.245, p<.01), as well as promotion on performance (β = 0.813, t = 5.300, p<.01). However, the impact of assessment practices on performance was insignificant (β = 0.524, t = 2.756, p<.01). The study concludes that employee training and promotion practices predict the performance of non-family employees in family-owned organizations in Kenya. Hence, organizations should invest in developing non-family employees to enhance both individual staff performance and organizational productivity.